Angiogenic properties of the chemokine RANTES/CCL5. (21st November 2011) - Suffee, Nadine; Richard, Benjamin; Hlawaty, Hanna; Oudar, Olivier; Charnaux, Nathalie; Sutton, Angela
Abstract : Atherosclerosis is an inflammatory disease that is one of the leading causes of death in developed countries. This disease is defined by the formation of an atherosclerotic plaque, which is responsible for artery obstruction and affects the heart by causing myocardial infarction. The vascular wall is composed of three cell types and includes a monolayer of endothelial cells and is irrigated by a vasa vasorum. The formation of the vascular network from the vasa vasorum is a process involved in the destabilization of this plaque. Cellular and molecular approaches are studied by in vitro assay of activated endothelial cells and in in vivo models of neovascularization. Chemokines are a large family of small secreted proteins that have been shown to play a critical role in the regulation of angiogenesis during several pathophysiological processes such as ischaemia. Chemokines may exert their regulatory activity on angiogenesis directly by activating the vasa vasorum, or as a consequence of leucocyte infiltration through the endothelium, and/or by the induction of growth factor expression such as that of VEGF (vascular endothelial growth factor). The present review focuses on the angiogenic activity of the chemokines RANTES (regulated upon activation, normal T-cell expressed and secreted)/CCL5 (CC chemokine ligand 5). RANTES/CCL5 is released by many cell types such as platelets or smooth muscle cells. This chemokine interacts with GPCRs (G-protein-coupled receptors) and GAG (glycosaminoglycan) chains bound to HSPGs (heparan sulfate proteoglycans). Many studies have demonstrated, using RANTES/CCL5 mutated on their GAG or GPCR-binding sites, the involvement of these chemokines in angiogenic process. In the present review, we discuss two controversial roles of RANTES/CCL5 in the angiogenic process.